MAHASISWA PENGGUNA MEDIA SOSIAL (STUDI TENTANG FUNGSI MEDIA SOSIAL BAGI MAHASISWA FISIP UR) - Sari Melati; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study entitled University Students as Social Media Users (A Study on The Social Media Function for Students of Social and Political Sciences Faculty, Riau University). This study interested to conduct this topic because of the phenomenon of social media usage arround the writer. Afterwards, this study wanted to find out what the most popular social media in Faculty of Social and Political Sciences, Riau University. It related to the reason in choosing the social media for university students.To find out the result of this study, the writer used data collect technique by using observation, and questionnaire. The way how the writer took the sample or respondent is quota sampling technique. In determining quota sampling as many as 10 people for each International Relationship, Public Administration, Bussiness Administration, and Tourism major. Then as many as 15 people for each Sciences of Government, Communication, and Sociology. So that, gets the total respondent was 85 people. The method used is descriptive quantitative.The result of this study showed that the most popular social media for university students of Faculty of Social and Political Sciences was instagram. Because they tended to keep abreast of the times and easier to use than other kind of social media. Whereas besides the function of social media was forming cybercommunity, for university students the function of social media was the source of information and entertain. The result of this study is expected to be able to provide and overview to all those who need information about University Students as Social Media Users.Keywords : University Students, User, Social Media